2015
DOI: 10.15288/jsad.76.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Sexual Orientation Disparities in Tobacco and Alcohol Use

Abstract: ABSTRACT. Objective: The purpose of this study was to examine whether the composition of social networks contributes to sexual orientation disparities in substance use and misuse. Method: Data were obtained from the National Longitudinal Study of Adolescent Health (Add Health), a nationally representative cohort study of adolescents (N = 20,745). Wave 1 collected extensive information about the social networks of participants through peer nomination inventories. Results: Same-and both-sex-attracted youths had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
7
1
Order By: Relevance
“…Adaptive personality traits (e.g., being ambitious, open to new experiences, less narcissistic) mitigated the adverse relationship between discrimination and alcohol misuse among SMY [49]. At least one study [38] found that connection to the sexual minority community was protective, while other studies either only found this association among a subset of SMY (e.g., gay-identified youth) or found no association at all [50, 51, 45, 52]. This inconsistency in findings may be partially explained by differences in peer group drinking norms [50, 53].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adaptive personality traits (e.g., being ambitious, open to new experiences, less narcissistic) mitigated the adverse relationship between discrimination and alcohol misuse among SMY [49]. At least one study [38] found that connection to the sexual minority community was protective, while other studies either only found this association among a subset of SMY (e.g., gay-identified youth) or found no association at all [50, 51, 45, 52]. This inconsistency in findings may be partially explained by differences in peer group drinking norms [50, 53].…”
Section: Resultsmentioning
confidence: 99%
“…At least one study [38] found that connection to the sexual minority community was protective, while other studies either only found this association among a subset of SMY (e.g., gay-identified youth) or found no association at all [50, 51, 45, 52]. This inconsistency in findings may be partially explained by differences in peer group drinking norms [50, 53]. Parental attachment moderated the relationship between bisexual identity and HED risk in at least one study [10].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a fairly robust literature on the importance of social networks as a determinant of tobacco use (1214), there is a paucity of research on the role of such networks in explaining sexual orientation-related disparities in tobacco use (15). Social networks, in particular household members, have been identified as a critical aspect of smoking initiation, continued use, cessation, and relapse (16, 17).…”
Section: Introductionmentioning
confidence: 99%